2017
DOI: 10.1007/s11523-017-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy with Cytokine-Induced Killer Cells

Abstract: Cytokine-induced killer (CIK) cells form under certain stimulation conditions in cultures of peripheral blood mononuclear cells (PBMCs). They are a heterogeneous immune cell population and contain a high percentage of cells with a mixed T-NK phenotype (CD3+CD56+). The ready availability of a lymphocyte source, together with the high proliferative rate and potent anti-tumor activity of CIK cells, has allowed their use as immunotherapy in a wide variety of neoplasms. Cytotoxicity mediated by CD3+CD56+ T cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…The results of CD3 and CD56 phenotypes showed a very significant increase in expression versus culture duration. This finding was supported by Mata-Molanes et al [17], who reported that after 14 days of culture, the percentage of CD3 + CD56 + subset reaches 20 to 30% of the total CIK cells. Guo et al [30], who cultured CIK cells from healthy volunteers' blood donors for 14 days, reported CD3 + CD56 + proportion on day 14 as 25.31 ± 7.42%.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results of CD3 and CD56 phenotypes showed a very significant increase in expression versus culture duration. This finding was supported by Mata-Molanes et al [17], who reported that after 14 days of culture, the percentage of CD3 + CD56 + subset reaches 20 to 30% of the total CIK cells. Guo et al [30], who cultured CIK cells from healthy volunteers' blood donors for 14 days, reported CD3 + CD56 + proportion on day 14 as 25.31 ± 7.42%.…”
Section: Discussionsupporting
confidence: 65%
“…CIK cells, as the most frequently used ACT, are a heterogeneous cell population including natural killer T (NKT) cells (CD3 + CD56 + ), T cells (CD3 + CD56 − ), and NK cells (CD3 − CD56 + ) cells. Normally, the most cytotoxic cells with double T/NK phenotype are uncommon but present (1% to 5%) in circulating blood [16]; yet, after in vitro expansion for 14 days, they may reach 20 to 30% of the total CIK cells [17]. Most of these NKT cells have been shown to be derived from the T cells and not from NK cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have confirmed survival benefit and safety of CIK cell immunotherapy for patients with cancers. 14,25 Recently, the role of CIK cell treatment in patients with CRC was also reported. 22,[26][27][28] However, to date, there is only one study on the therapeutic effects of adjuvant CIK cell treatment in patients with CRC after surgery, and their results were limited by small sample size and short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 A series of studies have demonstrated the efficacy of adoptive cell immunotherapy, including tumorinfiltrating lymphocytes, antigen-specific T lymphocytes, cytokine-induced killer (CIK) cells and chimeric antigen receptor (CAR) T cells. [8][9][10][11] Among them, CIK cells have characteristics of rapid proliferation, strong antitumor activity, broad spectrum of antitumor activity and minimal toxicity and have been demonstrated as effective in many tumors, 12 including CRC. 11,[13][14][15] Moreover, our previous studies demonstrated the feasibility and low toxicity of CIK cell treatment for several kinds of cancer, including hepatocellular carcinoma, 16 breast cancer, 17,18 epithelial ovarian cancer, 19 non-small-cell lung cancer 20 and nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%